The inventory archive of the marginals of the difference in the brazilian curricular research (Research, Society and Development, 2021)
For over three decades, we have witnessed the perspective of the Philosophy of Difference contamination, led by Deleuze & Guattari, as well as that of think⁸ers recognized as the damned in research in the field of psychoanalysis, anthropology, gender studies, education and the curricular field. In this sense, the movement of this writing happens due to the need to register this formative memory, as well as its rhizomatic lines of connection, as it is understood that these are still established in the cosmos in a spectral state. In making this movement, we opted for the archive methodology as established by Derrida, in order to problematize the multiple possibilities of knowing these encounters.